ENVIRONMENTAL TOXICANTS IN SOILS AND WATERS OF SELECTED INDUSTRIAL AREAS IN NIGERIA. - Mustapha, Aliru; Adeyemi, Deborah (IJRDO-Journal of Applied Science, 2021)
Soil and water samples were taken from different industrial locations typically polluted by environmental toxicants in Nigeria to study the presence of environmental toxicants, human exposure and their health effects on man, plant and animals. Soil analyses for colour, compaction, moisture and pH profile as well as water conductivity chloride, hardness, chemical oxygen demand, phosphate, alkalinity, sulphate, and potentially harmful elements (Ni, Zn, Pb, Fe, Cr, Cu, Mn, Ba, As, Co and Se) were carried out using the Atomic Absorption Spectrophotometry (AAS), Association of Officials of Analytical Chemists (AOAC). Bacteriological analysis for the presence of Escherichia coli and infrared detection of carbon hydrogen, oxygen, nitrogen and sulphur were also studied. Results showed the water and soil pH range of 3.08 to 3.80 and may be unsuitable for planting as against pH of 5.5 to 7.0 that can support plant growth. The levels of zinc (0.59 mg kg−1); Ni (0.24 mg kg−1); Se (0.9 mg kg−1) and lead (0.15 to 0.91 mg kg−1) dissolution into the water and soil samples were similarly observed with the lead permissible dose varies between 0.05 to 0.51 mg kg−1. The analysis describes the percentage of both positive and negative effects of these chemicals as 55.3% and 45.94%, respectively. Apart from the higher acidic content above permissible levels of some trace metals in all samples, the microbiological presence of Escherichia coli bacteria in all the samples can only serves as potential dangers to human health.